Development of virtual environments using technological tools and resources to achieve meaningful Teaching-learning process for Foreign Languages - Sánchez Vásquez, Katherine Vanessa (2024)
The effect of the unpredictable pandemic due COVID-19 caused that face-to-face classes stop in many academic institutions around the world, including El Salvador. As a result of that unexpected situation, the necessity of using technology when teaching appeared. But, how can virtual environments be prepared to teach? It is in that way that in this academic paper it is discussed the impact of the pandemic on the education, especially in El Salvador and how the University of El Salvador face it. In addition to that, as an answer to the need of changing to virtuality, it presents a compilation of theoretical model, such as Leflore’s theory presentations, to fundament virtual environments giving them the capacity to mediate the relationship between teachers, students and content achieving harmony in virtuality. Also, it describes educational applications and tools for the teaching of a foreign language, and design of didactic material in order to create the best conditions for teachers and students when using virtual spaces. The most important Learning Management Systems, virtual tools, and theories were analyzed and describe so the reader can find useful resources to achieve a meaningful teaching-learning process for foreign languages when using virtual environments.